2019
DOI: 10.1097/dcr.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Score Adjusted Comparison of Pelviperineal Morbidity With and Without Omentoplasty Following Abdominoperineal Resection for Primary Rectal Cancer

Abstract: BACKGROUND: Abdominoperineal resection is associated with a high incidence of perineal complications, and whether this is reduced by an omentoplasty is still unclear. OBJECTIVE: This study aimed to investigate the impact of omentoplasty on pelviperineal morbidity in patients undergoing abdominoperineal resection for rectal cancer. DESIGN: This was a retrospective comparative cohort study using propensity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…The higher perineal hernia rate after OP is in line with previous studies [7,8]. Although a causal relation cannot be confirmed, the hypothesis is that the pedicled omentum will function as a large amount of loose fatty tissue that will easily descend through the pelvic outlet in the absence of a pelvic floor, while a few loops of small bowel are restricted by a certain mesenteric length in the possibility of herniating at the level of the perineum.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The higher perineal hernia rate after OP is in line with previous studies [7,8]. Although a causal relation cannot be confirmed, the hypothesis is that the pedicled omentum will function as a large amount of loose fatty tissue that will easily descend through the pelvic outlet in the absence of a pelvic floor, while a few loops of small bowel are restricted by a certain mesenteric length in the possibility of herniating at the level of the perineum.…”
Section: Discussionsupporting
confidence: 87%
“…It could therefore be that a true effect may not be demonstrated due to relatively low numbers. However, as only few patients would require surgical management, and this study as well as two recent large studies showed no significant reduction in reoperation rate for ileus [7,8], it is questionable whether this potential effect of OP would be clinically relevant.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Blok et al in a retrospective study of 106 patients who underwent an omentoplasty, demonstrated that omentoplasty did not lower the incidence or duration of perineal morbidity in patients undergoing abdominoperineal resection for rectal cancer. Additionally, they found that the omentoplasty itself was associated with a risk for reoperation (37).…”
Section: Discussionmentioning
confidence: 99%